Prevalence of anemia in the Portuguese adult population: results from the first National Health Examination Survey (INSEF 2015) - Samões, Catarina (2021)
Aims: Anemia is a global public health problemwith relevant adverse health, social and economic consequences. The objective of this study was to analyze the distribution of the prevalence of anemia in the Portuguese population. Methods: This is a cross-sectional population-based study, based on the first Portuguese National Health Examination Survey (INSEF), which included 4812 participants aged 25 to 74 years, with data on hemoglobin levels and self-reported diagnosis of anemia. The socioeconomic status of participants was assessed by education level, employment status and material deprivation. The association between socioeconomic factors and anemia was estimated by adjusted prevalence ratios. Results: The prevalence of anemia overall was 5.8%, 3.1% in men and 8.4% in women. The overall prevalence of moderate–severe anemia was 1.1%. Previously undiagnosed cases represented 92.5%. In men, anemia was associated with age, education, occupation and material deprivation, and in women, with age group and urban typology. Conclusion: Anemia represents a relevant public health issue in Portugal. In women, it is more prevalent among those of childbearing age and older, and in men among older individuals of low socioeconomic status. This information is relevant for developing targeted strategies aimed at the prevention, diagnosis and treatment of anemia.